Negative and positive photodielectric effects in quantum paraelectric BaFe12O19 single crystals. Issue 46 (14th November 2018) - Yin, L. H.; Hu, L.; Yang, J.; Teng, P.; Song, W. H.; Dai, J. M.; Zhu, X. B.; Sun, Y. P.
Abstract : Low-temperature negative and high-temperature positive photodielectric effects were observed in quantum paraelectric BaFe12 O19 single crystals. Abstract : The effects of light illumination on dielectric properties were investigated in ferrimagnetic quantum paraelectric BaFe12 O19 single crystals. The enhancement and reduction of dielectric constants under light illumination, i.e., positive and negative photodielectric (PD) effects, were found in BaFe12 O19 . The high-temperature positive PD effect depends significantly on the frequency and temperature, which can be ascribed to the photo-excitation accelerated electron hopping process between Fe 2+ and Fe 3+ . The low-temperature negative PD effect is nearly frequency-independent and is associated with non-polar tendency of the FeO5 bipyramids induced by photo-excited carriers. These findings could suggest a promising route to generate large and frequency-independent PD effects for application in photo-sensing devices.